An Investigation Into the Existence of Child Sex Abuse Policies Within Youth Sport Day Camps - Dennis A. Johnson (Journal of Applied Sports Management, 2014)
In light of the recent childhood sexual abuse (CSA) stories, this investigation involved semi-structured interviews of the directors of five youth sport day camps (n=5) serving a total of approximately 300 children. The purpose was to determine if camp directors developed camp policy/procedures, oriented the staff with regard to childhood sexual abuse, and if they had a documented plan should allegations of CSA occur. Results indicate that day camp directors in this sample do not have a written policy or procedures to deal with CSA issues, and they do not hold staff orientation to discuss safeguarding campers. Nearly all of the directors struggled to disclose how they would deal with a claim of sex abuse issue should one arise. Implications from this sample indicate a need for further study; meanwhile, sport managers might utilize best practices chronicled as a template for youth sport day camp directors to follow.
Keywords: childhood sexual abuse; youth sport; day camps; coach education